LCC111: English for Communicative Competence I - UiTM, Academy of Language Studies (2023)
This course aims to develop the communication strategies; reception, production, interaction and language competence skills to help students improve their proficiency from CEFR B1 (low) to CEFR B1 (high). This is to enable them to perform effectively and competently in the personal domain through the integration of the language skills (listening, reading, speaking, writing).